Meeting with the President of Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
CCAFS Science Officer for South Asia, Gopal Datt Bhatta meets with the President of Nepal, his Excellency Dr. Rambaran Yadav in Kathmandu, Nepal.